Cultures of risk and their influence on birth in rural British Columbia - Kornelsen, Jude (BioMed Central, 2012)
BACKGROUND: A significant number of Canadian rural communities offer local maternity services in the absence of caesarean section back-up to parturient residents. These communities are witnessing a high outflow of women leaving to give birth in larger centres to ensure immediate access to the procedure. A minority of women choose to stay in their home communities to give birth in the absence of such access. In this instance, decision-making criteria and conceptions of risk between physicians and parturient women may not align due to the privileging of different risk factors. METHODS: In-depth qualitative interviews and focus groups with 27 care providers and 43 women from 3 rural communities in B.C. RESULTS: When birth was planned locally, physicians expressed an awareness and acceptance of the clinical risk incurred. Likewise, when birth was planned outside the local community, most parturient women expressed an awareness and acceptance of the social risk incurred due to leaving the community. CONCLUSIONS: The tensions created by these contrasting approaches relate to underlying values and beliefs. As such, an awareness can address the impasse and work to provide a resolution to the competing prioritizations of risk.